Próba określenia wczesnej i późnej samoistnej restytucji oraz fazy superkompensacji po wysiłku wytrzymałościowym na przykładzie mężczyzny w 6 dekadzie życia. Opis przypadku - Mirosław Mrozkowiak (Kazimierz Wielki University, 2015)
Mrozkowiak Mirosław. Próba określenia wczesnej i późnej samoistnej restytucji oraz fazy superkompensacji po wysiłku wytrzymałościowym na przykładzie mężczyzny w 6 dekadzie życia. Opis przypadku = An attempt to determine the early and late spontaneous restitution and supercompensation phase after endurance effort on the example of a man in his sixties. A case study. Journal of Education, Health and Sport. 2015;5(9):63-94. ISSN 2391-8306. DOI10.5281/zenodo.29905 http://dx.doi.org/10.5281/zenodo.29905 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A63-94 https://pbn.nauka.gov.pl/works/615767 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 24.08.2015.   Próba określenia wczesnej i późnej samoistnej restytucji oraz fazy superkompensacji po wysiłku wytrzymałościowym na przykładzie mężczyzny w 6 dekadzie życia. Opis przypadku An attempt to determine the early and late spontaneous restitution and supercompensation phase after endurance effort on the example of a man in his sixties. A case study.   Mirosław Mrozkowiak   Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej Zdrowia, ul. Ogińskiego 16, Bydgoszcz   Słowa kluczowe: wysiłek wytrzymałościowy, wczesna i późna samoistna restytucja, faza superkompensacji.   Streszczenie Wstęp. Interpretacja aktywności w kontekście teorii stresu wydaje się kompleksowa i dobrze opisująca zjawiska zachodzące w organizmie. Jednym z problemów treningu fizycznego nie tylko 20-30 letniego ale i 60-70 letniego człowieka jest wybór właściwego pod względem objętości, intensywności i specyfiki obciążenia oraz właściwej formy i czasu wypoczynku. Celem badań jest określenie indywidualnych ram czasowych fazy wczesnej i późnej restytucji oraz fazy superkompensacji u mężczyzny w 6 dekadzie życia po wysiłku wytrzymałościowym. Opis przypadku.  Materiał i metody. Badany mężczyzna realizujący zdrowy styl życia poddał się oznaczeniu wybranych 46 wskaźników krwi po wysiłku wytrzymałościowym w czasie restytucji samoistnej. Uzyskane wyniki. Pozytywne wyniki zaobserwowano w większości mierzonych cech krwi. Przy czym różnie prezentowała się ich konfiguracja w trakcie 5 dniowego cyklu pomiarowego, określająca fazę wczesną, późną i superkompensacji Wnioski. (1) Pierwsza faza (szybka) restytucji po wysiłku wytrzymałościowym u mężczyzny w 6 dekadzie życia kończy się zależnie od analizowanej cechy krwi w pierwszej, drugiej lub trzeciej godzinie, druga faza (wolna) w wielu przypadkach badanych cech     kończy się po 45 godzinie od zakończenia pracy, (2)Na podstawie analizowanych cech nie można jednoznacznie określić czasu występowania fazy superkompensacji, ale jak należy sadzić w przypadku probanta jest to 33 godzina od zakończenia pracy, (3) Dla określenia dokładniejszych stref czasowych występowania wczesnej i późnej restytucji wymagane są badania na stosunkowo większej populacji i po wysiłkach fizycznych angażujących odmienne zdolności motoryczne o różnych parametrach, płci i wieku.     Key words: endurance effort, early and late spontaneous restitution, supercompensation phase.   Summary Introduction. The interpretation of physical activity in light of stress theory seems comprehensive and well suited to describe the processes taking place within the human body. One of the problems inherent in physical training, and encountered not only by the individuals in their twenties or thirties but also in their sixties and seventies, is the choice of a proper - in terms of volume, intensity and specificity - exercise load as well as form and time of rest. The aim of the present study is to determine individual time frames of the early and late restitution and supercompensation phase after endurance effort in a man in his sixties. A case study. Material and methods. The studied male individual who lives a healthy life-style subjected himself to the markings of 46 selected blood indicators conducted after endurance effort in the spontaneous restitution phase. Results. Positive results were observed in most of the blood features. However, their configuration within the 5-day measurement cycle varied and thus allowed one to determine both the early and late restitution and supercompensation phase. Conclusions. (1) In a man in his sixties the first (fast) restitution phase after endurance effort ends, depending on the analysed blood feature, in the first, second or third hour after finished effort; the second phase (slow), as observed in many of the measured blood features, ends 45 minutes after finished effort. (2) Based on the analyzed blood features, however, one cannot unambiguously determine the time occurrence of supercompensation phase; nevertheless, one may assume that for the studied individual it occurs thirty-three hour after finished effort. (3) In order to more accurately determine time frames of the early and late restitution, the research on a relatively larger population of varied sex and age is required; such a research would have to be conducted both before and after the physical efforts and it would have to engage various motoric functions of the studied individuals.